Nitrogen sources and net growth efficiency of zooplankton in three Amazon River plume food webs. (12th November 2015) - Loick‐Wilde, Natalie; Weber, Sarah C.; Conroy, Brandon J.; Capone, Douglas G.; Coles, Victoria J.; Medeiros, Patricia M.; Steinberg, Deborah K.; Montoya, Joseph P.
Abstract: The plasticity of nitrogen specific net growth efficiency (NGE) in marine mesozooplankton is currently unresolved, with discordant lines of evidence suggesting that NGE is constant, or that it varies with nitrogen source, food availability, and food quality in marine ecosystems. Specifically, the fate of nitrogen from nitrogen fixation is poorly known. We use 15 N : 14 N ratios in plankton in combination with hydrological data, nutrient profiles, and nitrogen fixation rate measurements to investigate the relationship between new nitrogen sources and the nitrogen specific NGE in three plankton communities along the outer Amazon River plume. The NGE of small (200–500 μm) mesozooplankton was estimated from the δ 15 N differences between particulate nitrogen and zooplankton using an open system Rayleigh fractionation model. The transfer efficiency of nitrogen among larger (> 500 μm) mesozooplankton was estimated from the change in δ 15 N as a function of zooplankton size. The Amazon River was not a significant source of bioavailable nitrogen anywhere in our study region, and subsurface nitrate was the primary new nitrogen source for the outer shelf community, which was dominated by diatoms. N2 fixation was the principal new nitrogen source at sites of high diatom diazotroph association abundance and at oceanic sites dominated by Trichodesmium spp. and Synechococcus spp. Although we found clear spatial differences in food quantity, food quality, and diazotroph inputs into mesozooplankton, our data show no significant differences in mesozooplankton nitrogen transfer efficiency and NGE (for latter, mean ± SD: 59 ± 10%) among sites.